2015
DOI: 10.1177/1040638715590652
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma in a wild black rat snake (Pantherophis alleghaniensis)

Abstract: Reports of neoplasia in captive reptiles are becoming more frequent; however, there is still scarce knowledge of the occurrence of neoplasia in wild reptiles. A wild black rat snake ( Pantherophis alleghaniensis) was presented to the Zoological Medicine service of the University of Georgia’s Veterinary Teaching Hospital with a 3 cm in diameter solid mandibular mass that was partially ulcerated. Radiographically, the mass was radiopaque with small bone spicules and partial osteolysis of the adjacent mandible. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The presence of this benign neoplasic modification is reported here for the first time in the dinosaurian fossil record, as well as in the fossil record overall. The occurrence of ameloblastoma is a well-known phenomenon in humans 37 and other mammals 38 , yet has only recently been identified among reptiles in the living wild black rat snake 39 . A related disorder, adenoameloblastoma, was noted in the Indian rock python 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this benign neoplasic modification is reported here for the first time in the dinosaurian fossil record, as well as in the fossil record overall. The occurrence of ameloblastoma is a well-known phenomenon in humans 37 and other mammals 38 , yet has only recently been identified among reptiles in the living wild black rat snake 39 . A related disorder, adenoameloblastoma, was noted in the Indian rock python 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The skeletal tumours that have been identified are the following: osteoma, ameloblastoma, ossified fibroma, osteosarcoma, osteochondroma and chondrosarcoma 40,41,55,77,80 . Studies have shown malignant entities to be dominant among neoplasms in NARs, at approximately 80% of all diagnosed neoplasms (83.3% in Page-Karjian et al, 76% in Ramsay et al) 81,82 .…”
Section: Differential Diagnosis Based On Phylogenetic Disease Bracketmentioning
confidence: 99%
“…Diagnosis of DGCT in this rhinoceros was largely made based on the histological and immunohistochemical features from human oncology and pathology as compiled in Table 1 . From the differential diagnoses, PIOSCC, SCC and ameloblastoma were ruled out, as these tumors do not feature ghost cell lesions [ 12 ]. GCOC was ruled out mainly by the fact that histopathological examination showed low mitotic activity, suggestive of a benign cellular status.…”
Section: Discussionmentioning
confidence: 99%